Differences in primary health care delivery to Australia's Indigenous population: a template for use in economic evaluations - Ong Katherine S; Carter Rob; Kelaher Margaret; Anderson Ian (BMC, 2012)
Abstract Background Health economics is increasingly used to inform resource allocation decision-making, however, there is comparatively little evidence relevant to minority groups. In part, this is due to lack of cost and effectiveness data specific to these groups upon which economic evaluations can be based. Consequently, resource allocation decisions often rely on mainstream evidence which may not be representative, resulting in inequitable funding decisions. This paper describes a method to overcome this deficiency for Australia's Indigenous population. A template has been developed which can adapt mainstream health intervention data to the Indigenous setting. Methods The 'Indigenous Health Service Delivery Template' has been constructed using mixed methods, which include literature review, stakeholder discussions and key informant interviews. The template quantifies the differences in intervention delivery between best practice primary health care for the Indigenous population via Aboriginal Community Controlled Health Services (ACCHSs), and mainstream general practitioner (GP) practices. Differences in costs and outcomes have been identified, measured and valued. This template can then be used to adapt mainstream health intervention data to allow its economic evaluation as if delivered from an ACCHS. Results The template indicates that more resources are required in the delivery of health interventions via ACCHSs, due to their comprehensive nature. As a result, the costs of such interventions are greater, however this is accompanied by greater benefits due to improved health service access. In the example case of the polypill intervention, 58% more costs were involved in delivery via ACCHSs, with 50% more benefits. Cost-effectiveness ratios were also altered accordingly. Conclusions The Indigenous Health Service Delivery Template reveals significant differences in the way health interventions are delivered from ACCHSs compared to mainstream GP practices. It is important that these differences are included in the conduct of economic evaluations to ensure results are relevant to Indigenous Australians. Similar techniques would be generalisable to other disadvantaged minority populations. This will allow resource allocation decision-makers access to economic evidence that more accurately represents the needs and context of disadvantaged groups, which is particularly important if addressing health inequities is a stated goal.